2020
DOI: 10.3390/membranes10120399
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Electroplating Wastewater Using NF pH-Stable Membranes: Characterization and Application

Abstract: Industrial adoption of nanofiltration (NF) for treatment of low-pH wastewater is hindered by the limited membrane lifetime at strongly acidic conditions. In this study, the electroplating wastewater (EPWW) filtration performance of a novel pH-stable NF membrane is compared against a commercial NF membrane and a reverse osmosis (RO) membrane. The presented membrane is relatively hydrophobic and has its isoelectric point (IEP) at pH 4.1, with a high and positive zeta potential of +10 mV at pH 3. A novel method w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Moreover, these results showed that these membranes have high acidic properties. In the case of the PES membranes, this could be due to the negatively charged sulfonic acid group in the polymer structure [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, these results showed that these membranes have high acidic properties. In the case of the PES membranes, this could be due to the negatively charged sulfonic acid group in the polymer structure [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Membrane A was coated by hand and has a MWCO between 600 and 800 Da, while Membrane B was coated by machine and had a MWCO around 500 Da. The MWCO of these membranes was determined using a protocol described in the previous work of Hegoburu et al, in which a mixture of probe PEG molecules at MW different fractions was used [19]. Membrane C was a commercial polyethersulfone membrane with a MWCO in the range of 500-600 Da, which can be used in the entire pH range of 0-14 [14,20].…”
Section: Membranesmentioning
confidence: 99%
“…Alternatively, or to supplement the methods listed above, membrane filtration techniques can also be used to treat galvanic wastewater [ 13 , 14 , 15 ]. Such techniques, in accordance with the concept of the Best Available Techniques (BAT), are among the primary elements of clean (i.e., zero waste) technologies, ensuring that up to 60% of the treated water is recirculated and heavy metals are removed from wastewater.…”
Section: Introductionmentioning
confidence: 99%